Transesterificação de óleo de soja com carbonato de dimetila catalisada por metóxido de potássio - Celante, Dian (2017)
World biodiesel production is growing up every year mainly due to government policies that require its consumption. However, biodiesel self-cost still makes it uncompetitive compared to petrodiesel, and one of the reasons is the chemical route currently used for its production, which generates glycerol as a co-product. As a result, alternative chemical routes have emerged, such as transesterification with dimethyl carbonate using alkaline catalysts. Therefore, the aim of this work was to evaluate the transesterification reaction of soybean oil with dimethyl carbonate catalyzed by potassium methoxide to produce biodiesel. A recrystallization process of the catalyst was developed in the presence of methanol. Reaction variables were evaluated as time, temperature, reagent molar ratio and catalyst concentration. The best condition was 80 °C, 6: 1 dimethyl carbonate to oil molar ratio and 2wt% of catalyst relative to oil for 15 minutes of reaction with a triglycerides conversion higher than 99%. Methanol influence on the reaction medium was also investigated. Besides, the comparison between catalyzed reactions with the recrystallized and non-recrystallized catalyst was performed, resulting in higher conversions for recrystallized catalyst. Potassium quantification in the biodiesel phase was also carried out, indicating that a washing step in the biodiesel was necessary to remove the catalyst. Recrystallization process showed to be efficient and increased the reaction rate, consuming all soybean oil in a short time.